Macroporous three-dimensional MXene architectures for highly efficient solar steam generation. Issue 17 (8th April 2019) - Zhao, Xing; Zha, Xiang-Jun; Pu, Jun-Hong; Bai, Lu; Bao, Rui-Ying; Liu, Zheng-Ying; Yang, Ming-Bo; Yang, Wei
Abstract : 3D MXene architectures combining the high light absorption ability of MXenes and porous melamine foam exhibit efficient solar steam generation. Abstract : Efficient utilization of abundant solar energy for steam generation is an attractive, renewable, and environment-friendly technology for seawater desalination and wastewater purification, enabling solutions to address the global long-standing water scarcity issues. However, the low energy efficiency, high cost and complex systems with multiple components of state-of-the-art technologies hindered their practical applications. Herein, we report the first example of three-dimensional (3D) MXene architecture (3DMA)-based solar steam generators via a facile two-step dip coating process without any annealing or high temperature carbonization. The 3DMAs prepared by a cost-effective, scalable, simple fabrication method show effective broadband solar absorption (∼98%) and excellent solar thermal conversion ability based on 2D to 3D morphological transformation of MXenes, making good use of intrinsic theoretical photothermal performance of MXenes. The particularly hydrophilic nature of MXenes and the macroporous structure of melamine foam allow continuous water supply to 3DMAs owing to their strong capillary effect. As a result, the 3DMAs achieve water evaporation rates of 1.41 and 7.49 kg m −2 h −1 under solar illumination of 1 sun and 5 sun with a superb solar steam efficiency of up to 88.7% and 94.2%, respectively. This scalable 3DMA can be used to produce clean water from both seawater and wastewater with rejections close to 100% for organic dyes and metal ions. This work creates a platform to develop novel composite materials for solar-driven seawater desalination and wastewater purification via opening a new window for the utilization of MXenes as photothermal agents in practical applications.